Removal of Airway Foreign Body in a Premature Neonate. (October 2021) - Reed, Leighton; Larson, Stephen; Sheyn, Anthony; McLevy, Jennifer
Objective: Airway foreign bodies are the leading cause of infantile deaths and fourth among preschool children. Airway foreign bodies in extremely premature neonates represent a rare but potentially lethal entity. There are very few reports in the literature describing the treatment of such a condition in premature neonates. The objectives of this report are to describe the safe removal of an airway foreign body in an extremely premature infant using urologic instruments in a trans-endotracheal tube fashion and to review the literature for other techniques that have proven safe and effective, thereby adding technical options for future cases. Methods: We reviewed the case reported and reviewed pertinent literature. Results: A 2-week old, ex-24 3/7-week, 820-g pre-mature infant was intubated with a 2.5 endotracheal tube. After intubation, a 2-cm foreign body was discovered in the distal trachea by chest x-ray. The child's respiratory status continuously deteriorated with increasing oxygen and positive pressure requirements. While remaining intubated, the child underwent direct suspension laryngoscopy, the ventilator circuitry was disconnected, and the object was successfully removed using a 1.2 mm rigid ureteroscope and 1.1 mm grasping forceps through the 2.5 endotracheal tube. Conclusion: This case report demonstrates the effectiveness of using a 1.2 mm ureteroscope and 1.2 mm urologic graspers to extract an airway foreign body from an extremely premature neonate through an endotracheal tube without paralyzing the patient. This method provides a safe and effective means of visualizing and, if necessary, manipulating the airway in a population prone to respiratory complications.